Penerapan Pelaksanaan Pembelajaran Pada Masa Pandemi Dalam Program Kampus Mengajar 2 Di SMPN 13 Surakarta - Deya Inawijaya; Hermawati (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
Campus Teaching 2 (Kampus Mengajar 2) is a form of implementation of the Merdeka Learning Campus Merdeka (MBKM) program from the Ministry of Education, Culture, Research, and Technology in the form of teaching assistance to empower students in assisting the learning process in basic education in various villages or cities. The goal of this Teaching Campus is to present students as part of the process of strengthening literacy and numeracy, assisting learning during the pandemic, particularly in the 3T area, and providing solutions to schools for an effective learning process. Pandemic of Covid-19. This can be seen in the drop in enthusiasm in learning, students' level of knowledge of the learning process, literacy and numeracy skills, and at the distance learning school level, logistical issues severely limit the effectiveness of the learning process, as shown at SMP Negeri 13 Surakarta. Direct and online teaching, assisting with technology adaptation, and assisting school management are some of the approaches employed in the program. The activity's final result and influence is the development of student empathy for community problems, the ability to collaborate across fields and sciences, and the ability to strengthen the true role and contribution of universities and students in national development.a